# Violympic toán 8

Cho $\dfrac{1}{a}+\dfrac{1}{b}+\dfrac{1}{c}=\dfrac{1}{a+b+c}$ .CMR:

$\dfrac{1}{a^{1995}}+\dfrac{1}{b^{1995}}+\dfrac{1}{c^{1995}}=\dfrac{1}{a^{1995}+b^{1995}+c^{1995}}$

HELP ME !

Phùng Khánh Linh 30 tháng 11 2017 lúc 18:19

Xuất phát từ giả thiết , ta có :

$\dfrac{1}{a}+\dfrac{1}{b}+\dfrac{1}{c}=\dfrac{1}{a+b+c}$

=> $\dfrac{bc+ac+ab}{abc}=\dfrac{1}{a+b+c}$

=> $\left(a+b+c\right)\left(ab+bc+ac\right)=abc$

=> $\left(a+b+c\right)\left(ab+bc+ac\right)-abc=0$

=> $a\left(ab+bc+ac\right)+b\left(ab+bc+ac\right)+c\left(ab+bc+ac\right)-abc=0$=> a2b + abc + a2c + ab2 + b2c + abc + abc + bc2 + ac2 - abc = 0

=> ab(a + b) + ac( a + c) + bc( b + c) + 2abc = 0

=> ab( a + b + c) + ac( a + b + c ) + bc( b + c) = 0

=> ( a + b + c)a( b + c) + bc( b + c) = 0

=> ( b + c)( a2 + ab + ac + bc) = 0

=> ( b + c)( a + b)( c + a) = 0

Suy ra :

* b = -c

*a = -b

* c = -a

TH1 :Với b = -c

$VT=\dfrac{1}{a^{1995}}+\dfrac{1}{\left(-c\right)^{1995}}+\dfrac{1}{c^{1995}}=\dfrac{1}{a^{1995}}$

$VP=\dfrac{1}{a^{1995}+b^{1995}+c^{1995}}=\dfrac{1}{a^{1995}+\left(-c\right)^{1995}+c^{1995}}=\dfrac{1}{a^{1995}}=VT$

TH2 : với a = -b

$VT=\dfrac{1}{\left(-b\right)^{1995}}+\dfrac{1}{b^{1995}}+\dfrac{1}{c^{1995}}=\dfrac{1}{c^{1995}}$

$VP=\dfrac{1}{a^{1995}+b^{1995}+c^{1995}}=\dfrac{1}{\left(-b\right)^{1995}+b^{1995}+c^{1995}}=\dfrac{1}{c^{1995}}=VT$

TH3 . c = -a , Tương tự

Vậy , đẳng thức được Chứng minh

Bình luận (0)

Các câu hỏi tương tự